VISUAL SIGNS ON THE BILLBOARD OF BALI ARTS FESTIVAL XLV YEAR 2023 : PEIRCE SEMIOTICS ANALYSIS - Gede Bayu Segara Putra; I Kadek Jayendra Dwi Putra (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2024)
This study is aimed at examining the visual signs found on the billboard of the Bali Arts Festival XLV Year 2023 using Charles Sander Peirce's semiotics approach. In an effort to understand how messages are communicated to the audience, an analysis is conducted on the icons, indexes, and symbols that appear in the design of the billboard. Through qualitative descriptive methods, the visual elements in the billboard are separated and observed, then analyzed using Peirce's semiotics framework. The results of the analysis indicate that the theme "Segara Kerthi" (Ocean of Harmony) is successfully represented in the billboard by using icons such as the illustration of Gajah Mina, which symbolizes the protector of the sanctity of the sea, indexes such as the rising sun, which depicts hope and a new beginning, and symbols such as government logos and social media icons that reflect support and technological advancement. These visual signs provide profound meanings related to the protection and appreciation of the sea as a source of life and civilization. In conclusion, this analysis provides a deeper understanding of how the visual signs in this billboard create a strong cultural identity, educate, and capture the audience's attention. This research offers a positive contribution to the analysis of visual communication works and has the potential to be further developed with diverse theoretical approaches and disciplines.